Rekomendasi Audit Keselamatan Jalan terhadap Bangunan Pelengkap dan Perlengkapan Jalan - Brama Nalendra; Elita Amrina (Jurnal Talenta Sipil, 2023)
This paper presents a literature review regarding road safety audit recommendations, which were published between 2014 – 2019. This study aims to conduct a literature review regarding road safety audits in various locations in Indonesia and then summarize conclusions based on the recommendations given in terms of auxiliary buildings and road equipment. From these results it can be seen the tendency of road safety audit recommendations to see the potential for traffic accidents. Qualitative method is the method used in this study, which examines the quality of relationships, situations, and activities. The results of safety recommendations from the road safety audit in terms of complementary buildings and road equipment, many recommendations are proposed based on the recommendations of the audit results, such as traffic signs, safety fences, road markings, street lighting devices, and facilities for pedestrians, for this reason it is necessary to emphasize planning consultants, service providers and owners related to the realization of these recommendations to reduce the potential for traffic accidents caused by a lack of complementary buildings and road equipment.